Kualitas Pelayanan Administrasi Kependudukan pada Pendaftaran Kartu Keluarga dan Kartu Tanda Penduduk Elektronik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Karo - Br Naibaho, Intan Firayunia; Ginting, Simson (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
The purpose of this study is to find out and describe in detail the Quality of Population Administration Services on Registration of Family Cards and Electronic Identity Cards (KTP-el) at the Karo Regency Population and Civil Registration Office. The research method used is a qualitative method with a descriptive approach. Data collection techniques used in research are interviews, observation and documentation studies. The data obtained was then analyzed qualitatively with the quality indicators proposed by Zeithaml et.al., including Tangibles, Reliability, Responsiveness, Asssurance and Empathy. The results of research in the field can be concluded that for appearance, discipline, attitude, employee response is good, as well as guarantees, requirements and procedures have been given optimally and well in serving the community. While the office's physical facilities are not fully adequate to support the smooth running of services, employees are not careful and thorough which results in errors in population documents that are taken care of by the community which results in some people stating that the services provided are not appropriate and discriminatory employee attitudes are still found and there are brokers in the office Population and Civil Registration Office of Karo Regency. This shows that the quality of population administration services at the Karo Regency Population and Civil Registration Service is not entirely good.